2010
DOI: 10.1186/1743-422x-7-251
|View full text |Cite
|
Sign up to set email alerts
|

Newly discovered KI, WU, and Merkel cell polyomaviruses: No evidence of mother-to-fetus transmission

Abstract: BackgroundThree* human polyomaviruses have been discovered recently, KIPyV, WUPyV and MCPyV. These viruses appear to circulate ubiquitously; however, their clinical significance beyond Merkel cell carcinoma is almost completely unknown. In particular, nothing is known about their preponderance in vertical transmission. The aim of this study was to investigate the frequency of fetal infections by these viruses. We sought the three by PCR, and MCPyV also by real-time quantitative PCR (qPCR), from 535 fetal autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…18 Foetal tissues were also negative for WU and KI viruses. 25 In this study WU and KI viruses were not found in urine, plasma and respiratory samples collected during pregnancy. KIPyV DNA was detected in two plasma samples, but not in urine and respiratory samples from control, non pregnant women.…”
Section: Discussionmentioning
confidence: 72%
“…18 Foetal tissues were also negative for WU and KI viruses. 25 In this study WU and KI viruses were not found in urine, plasma and respiratory samples collected during pregnancy. KIPyV DNA was detected in two plasma samples, but not in urine and respiratory samples from control, non pregnant women.…”
Section: Discussionmentioning
confidence: 72%
“…MCC is a cutaneous cancer, and MCPyV has been recovered from normal skin of up to 40% of healthy adult volunteers, which would support cutaneous transmission of the virus (13,26). MCPyV was not detected in 535 fetal autopsy samples, and thus vertical transmission from mother to fetus does not occur or is very rare (24). However, this does not exclude the possibility of perinatal horizontal transmission at the time of birth.…”
Section: Discussionmentioning
confidence: 98%
“…Seroprevalence of 50-95% is reported in adults (7,(12)(13)(14)(25)(26)(27)(28)(29). The age-specific seroprevalence of MCPyV (Fig.…”
Section: Serologymentioning
confidence: 99%